Interesting case of cutaneous metastases to thoracic skin from anaplastic carcinoma of thyroid: An unreported entity in India - P Jemisingh; A N M. MaalikBabu; V Arumugam; Nirmaladevi Palanivel (Wolters Kluwer Medknow Publications, 2022)
Anaplastic thyroid carcinoma is a highly aggressive tumor with 100% mortality that constitutes 1%-2% of thyroid malignancies. Cutaneous metastases from thyroid carcinoma are extremely rare. We report a case of a 68-year-old male with anaplastic thyroid carcinoma with cervical lymph node and thoracic cutaneous metastases. Following the diagnosis of anaplastic carcinoma with stage IVB after thorough investigations, he was started on chemotherapy with cisplatin and adriamycin, and also radiotherapy was given subsequently. Dermatological examination showed a single ulcer of size 3 × 2 cm, hard nodules, and plaques of varied sizes present over the anterior chest. Skin biopsy from the nodule showed pleomorphic tumor cells in strands with colloid material and neutrophilic infiltrates in the deep dermis. The present case report demonstrates that thoracic skin metastases can occur from anaplastic thyroid carcinoma with nodules and ulcers and, to our knowledge, this is the first case report of such an extremely rare condition from India.